Statistics for physical science : an introduction - Martin, B. R. (Brian Robert) (Academic Press, 2012)
Statistical Methods for the Physical Sciences is an informal, relatively short, but systematic, guide to the more commonly used ideas and techniques in statistical analysis, as used in physical sciences, together with explanations of their origins. It steers a path between the extremes of a recipe of methods with a collection of useful formulas, and a full mathematical account of statistics, while at the same time developing the subject in a logical way. The book can be read in its entirety by anyone with a basic exposure to mathematics at the level of a first-year undergraduate student of physical science and should be useful for practising physical scientists, plus undergraduate and postgraduate students in these fields. - Problems at the end of each chapter - All the chapters contain worked examples - Collection of useful formulas in order to give a detailed account of mathematical statistics.